Relevansi Al-Qur'an dan Hadits Dalam Pembentukan Nilai Sosial, Etika Politik, dan Pengambilan Keputusan di Era Kontemporer: Kajian Terhadap Pengaruhnya Dalam Kehidupan Sosial, Kebijakan Publik, Demokrasi, Kepemimpinan, Hukum, Ekonomi, Pendidikan, dan Teknologi - Jannatul Firdausiyah; Ainur Rofiq Sofa (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to explore the relevance of the Qur'an and Hadith in shaping social values, political ethics, and decision-making in the contemporary era, highlighting their influence on various aspects of life, such as society, public policy, democracy, leadership, law, economics, education, and technology. In the modern context marked by global challenges, the values of the Qur'an and Hadith, such as justice, consultation (shura), honesty, and responsibility, provide a strong moral framework for creating a harmonious and civilized society. The findings indicate that the social values taught by Islam promote solidarity and respect for human rights, while the principles of political ethics emphasize trustworthiness and honesty in governance. In decision-making, consultation and justice are important, as they enable the creation of inclusive and democratic public policies. Moreover, the Islamic perspective on law emphasizes the protection of individual rights and social justice, while in economics, the teachings of the Qur'an and Hadith advocate for equitable wealth distribution and the elimination of usury. In the field of education, Islamic values integrate worldly and spiritual knowledge to shape a virtuous young generation, whereas, in technology, Islamic teachings offer ethical guidance for utilizing technological advancements for the betterment of humanity. This study concludes that the Qur'an and Hadith are not only relevant but also provide practical solutions to address modern challenges in various life sectors.